An IFC-to-CityGML Triple Graph Grammar - Tauscher, Helga (ECAADE-EDUCATION & RESEARCH COMPUTER AIDED ARCHITECTURAL DESIGN EUROPE, 2021)
36th International Conference on Education and Research in Computer Aided Architectural Design in Europe (eCAADe)